Autophagy-modulating phytochemicals in cancer therapeutics: Current evidences and future perspectives. (May 2022) - Patra, Srimanta; Mishra, Soumya R.; Behera, Bishnu P.; Mahapatra, Kewal K.; Panigrahi, Debasna P.; Bhol, Chandra S.; Praharaj, Prakash P.; Sethi, Gautam; Patra, Samir K.; Bhutia, Sujit K.
Abstract: Autophagy is an intracellular catabolic self-cannibalism that eliminates dysfunctional cytoplasmic cargos by the fusion of cargo-containing autophagosomes with lysosomes to maintain cyto-homeostasis. Autophagy sustains a dynamic interlink between cytoprotective and cytostatic function during malignant transformation in a context-dependent manner. The antioxidant and immunomodulatory phyto-products govern autophagy and autophagy-associated signaling pathways to combat cellular incompetence during malignant transformation. Moreover, in a close cellular signaling circuit, autophagy regulates aberrant epigenetic modulation and inflammation, which limits tumor metastasis. Thus, manipulating autophagy for induction of cell death and associated regulatory phenomena will embark on a new strategy for tumor suppression with wide therapeutic implications. Despite the prodigious availability of lead pharmacophores in nature, the central autophagy regulating entities, their explicit target, as well as pre-clinical and clinical assessment remains a major question to be answered. In addition to this, the stage-specific regulation of autophagy and mode of action with natural products in regulating the key autophagic molecules, control of tumor-specific pathways in relation to modulation of autophagic network specify therapeutic target in caner. Moreover, the molecular pathway specificity and enhanced efficacy of the pre-existing chemotherapeutic agents in co-treatment with these phytochemicals hold high prevalence for target specific cancer therapeutics. Hence, the multi-specific role of phytochemicals in a cellular and tumor context dependent manner raises immense curiosity for investigating of novel therapeutic avenues. In this perspective, this review discusses about diverse implicit mechanisms deployed by the bioactive compounds in diagnosis and therapeutics approach during cancer progression with special insight into autophagic regulation.